Pengaruh Citra Merek, Harga Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Smartphone Rds Phone Store Di Surakarta - Ramadhan Dicky Setiawan; Wuryaningsih Dwi Lestari (VALUE, 2023)
The purpose of this study was to determine the effect of brand image, price and product quality on purchasing decisions for Rds Phone Store smartphone products in Surakarta. This research uses descriptive quantitative research. The data source used in this research is primary data, in this study the data collection method used is using a questionnaire. The measurement scale used is the Likert scale. The population in this study were all Surakarta students who had bought and used smartphones. The sample of this study amounted to 100 people who are students in Surakarta who use smartphones. The sampling technique used in this study was non-probability sampling technique. The analysis used includes descriptive statistical analysis, instrument test, classical assumption test, hypothesis testing, and multiple linear regression analysis. In this study, the data were processed using SPSS. The results of this study are that the brand image variable has a positive and insignificant effect on purchasing decisions. The brand image of smartphone products at Rds Phone Store does not have a significant influence on purchasing decisions. The price variable has a significant positive effect on purchasing decisions. The better the price of smartphones offered at Rds Phone Store, the more consumers' purchasing decisions to buy these goods will increase. The product quality variable has a significant positive effect on purchasing decisions. The better the quality of the smartphone products offered at the Rds Phone Store, the positive impact on purchasing decisions made by consumers.